STUDENTS’ PERCEPTION OF USING FLASHCARD IN LEARNING ENGLISH VOCABULARY: A CASE STUDY AT AN ISLAMIC BOARDING SCHOOL - Thania Qothrun Nada (English Didactic, 2020)
Vocabulary is one of the most important aspects of learning English because it serves as the basis for speaking, reading and writing. Meanwhile, learning foreign languages is a challenge for learners and teachers as well. A teacher who teaches foreign languages needs to develop teaching methods which are not boring and one of the techniques is through games. It enables teachers to create a fun learning for the students. There are many types of games that can be applied in the teaching-learning process, one of them is a flashcard. Flashcard is a fun activity game in which students guess what they see in the picture, the students could also learn to concentrate and to think carefully. Thus, using games in vocabulary learning can create an enjoyable atmosphere. This research aims to investigate students’ perception on using flashcard in learning English vocabulary. This study employs a qualitative approach as a research design and was conducted at an Islamic boarding school in Indonesia. The participants of this research were seven females and eight male students in one of the English class in the 2nd grade of junior high school. The data were collected from interviews and Focus Group Discussions. This research used thematic analysis from Braun and Clarke (2006) as the data analysis method. The findings showed that participants expressed some perspectives on the benefits of using flashcard in learning English vocabulary, flashcards improve students’ interest in learning and enhance students’ vocabulary skills.